ANALISIS PENGARUH PENERAPAN GOOD CORPORATE GOVERNANCE TERHADAP EARNING MANAGEMENT (STUDI EMPIRIS PADA PERUSAHAAN SUBSEKTOR PROPERTI DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA) - B2092151003, HENGKY LEON (FAKULTAS EKONOMI DAN BISNIS UNTAN, 2017)
Corporate governance is a series of good relations between management, shareholders and allinterested parties against the company in order to optimize the value of the company in a professionalmanner. The purpose of the research is to want to measure the implementation of corporategovernance practices against earnings management on the company property and real estate werelisted on the Indonesia stock exchange. The size that is used consists of institusional ownershippercentage, the number of commissioners, the board of directors, the audit committee and the totalaccrual. Analysis tools are used in the research using the SPSS program. Method of determination ofsamples is purposive sampling where there are 107 observation data. The analysis used in the SPSSprogram be descriptive analysis, linearity test, normality test, multicollinearity test, heteroscedasticitytest, autocorrelation test, multiple linear regression, f test and t test. As for the results of the researchconducted is a regression model already are BLUE and have a specification of goodness fit model.Institusional ownership has no effect against the earnings management practices, the board ofcommissioners has no effect against the earnings management practices, the board of directors doesnot have an effect on earnings management practices and the audit committee of influential negativelyto earnings management practices.Keywords: corporate governance, institutional ownership, board of commissioner, board of director,audit committee, earning management